The stimulatory effect of the octadecaneuropeptide ODN on astroglial antioxidant enzyme systems is mediated through a GPCR - Hamdi, Yosra; Kaddour, Hadhemi; Vaudry, David; Douiri, Salma; Bahdoudi, Seyma; Leprince, Jérôme; Castel, Hélène; Vaudry, Hubert; Amri, Mohamed; Tonon, Marie-Christine; Masmoudi-Kouki, Olfa (Frontiers in Endocrinology, 2012)
Astroglial cells possess an array of cellular defense systems, including superoxide dismutase (SOD) and catalase antioxidant enzymes, to prevent damage caused by oxidative stress on the central nervous system. Astrocytes specifically synthesize and release endozepines, a family of regulatory peptides including the octadecaneuropeptide (ODN). ODN is the ligand of both central-type benzodiazepine receptors (CBR), and an adenylyl cyclase- and phospholipase C-coupled receptor. We have recently shown that ODN is a potent protective agent that prevents hydrogen peroxide (H2O2)-induced inhibition of SOD and catalase activities and stimulation of cell apoptosis in astrocytes. The purpose of the present study was to investigate the type of receptor involved in ODN-induced inhibition of SOD and catalase in cultured rat astrocytes. We found that ODN induced a rapid stimulation of SOD and catalase gene transcription in a concentration-dependent manner. In addition, 0.1 nM ODN blocked H2O2-evoked reduction of both mRNA levels and activities of SOD and catalase. Furthermore, the inhibitory actions of ODN on the deleterious effects of H2O2 on SOD and catalase were abrogated by the metabotropic ODN receptor antagonist cyclo1–8[Dleu5]OP, but not by the CBR antagonist flumazenil. Finally, the protective action of ODN against H2O2-evoked inhibition of endogenous antioxidant systems in astrocytes was protein kinase A (PKA)-dependent, but protein kinase C-independent. Taken together, these data demonstrate for the first time that ODN, acting through its metabotropic receptor coupled to the PKA pathway, prevents oxidative stress-induced alteration of antioxidant enzyme expression and activities. The peptide ODN is thus a potential candidate for the development of specific agonists that would selectively mimic its protective activity.